Korelasi Antara Hafalan Al-Qur’an dengan Hasil Belajar Bahasa Arab Santri - Hasna Tsabita; Hamdal; Muhammad Singgih (Program Studi Pendidikan Bahasa Arab, 2022)
Learning the Al-Qur'an is something that must be emphasized to Muslims, therefore reading and memorizing the Al-Qur'an is a recommendation for Muslims. Arabic is the main staple for Muslims because Arabic is the key to the broad repertoire of Islam, especially the Al-Qur’an. One of the Islamic education institutions in Lampung PTQA Umniyati Gunung Terang requires its students to memorize the Al-Qur’an and learn Arabic in their daily life, so that it aims to make PTQA Umniyati graduates memorize the Al-Qur'an who understands Arabic in order to facilitate understanding in Al-Qur'an and Sunnah. The formulation of the problem in this study is to find a correlation between memorization of the Al-Qur'an and the learning outcomes of Arabic students of class XII PTQA Umniyati Gunung Terang which aims to determine the extent of the correlation between memorization of Al-Qur'an students of class XII PTQA Umniyati. Based on the research objectives, this type of research is an associative quantitative study, with a saturated sample of 17 students. The data collection technique used in this research is through documentation. The analysis technique used is statistical analysis with the product moment correlation technique. Based on the data analysis, the calculation result is 0.856, that there is a relationship between memorization of the AQur'an and the learning outcomes of the students in class XII PTQA Umniyati Gunung Terang. This is evidenced by the analysis of the hypothesis test obtained with the results of rxy in the interval 0.70 - 0.90 with the criteria